2009
DOI: 10.1016/j.labeco.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of performance-related pay for teachers in England

Abstract: a b s t r a c tThis paper evaluates the impact of a performance-related pay scheme for teachers in England. Using data which matches individual pupils to individual teachers, and contains both test scores and value-added, we test whether the introduction of a payment scheme based on pupil attainment increased teacher effort. Our evaluation design controls for pupil effects, school effects and teacher effects, and adopts a difference-indifference methodology. We find that the scheme did improve test scores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 21 publications
1
92
0
5
Order By: Relevance
“…Lazear 2003a). Atkinson et al (2004) find that the introduction of performance-related pay had a substantial positive impact on student achievement in England (see also their survey of other studies, the more rigorous of which also tend to find a positive relationship between financial teacher incentives and student outcomes). Similarly, Lavy (2002,2004) has shown that monetary incentives for teachers based on their students' performance improved efficiency immensely in Israeli schools, with incentives for individual teachers being more efficient than teacher group incentives.…”
Section: Efficiencymentioning
confidence: 95%
“…Lazear 2003a). Atkinson et al (2004) find that the introduction of performance-related pay had a substantial positive impact on student achievement in England (see also their survey of other studies, the more rigorous of which also tend to find a positive relationship between financial teacher incentives and student outcomes). Similarly, Lavy (2002,2004) has shown that monetary incentives for teachers based on their students' performance improved efficiency immensely in Israeli schools, with incentives for individual teachers being more efficient than teacher group incentives.…”
Section: Efficiencymentioning
confidence: 95%
“…Figlio e Kenny (2006), por outro lado, com base na Pesquisa Longitudinal Nacional sobre Educação (NELSNational Education Longitudinal Study), encontraram resultados melhores em escolas com sistemas de incentivos, mas pela natureza dos dados não puderam descartar a possibilidade desses resultados terem sido causados pela adoção dos sistemas de incentivos pelas melhores escolas (FIGLIO; KENNY, 2006). Resultados mais convincentes foram encontrados por Winters et al (2008) em estudo do sistema de incentivos de Little Rock, Arkansas, onde os alunos dos professores incluí-dos no programa obtiveram ganhos substanciais (WINTERS et al, 2008), e por Atkinson et al (2009), na Inglaterra, onde o ganho equivalia a aproximadamente 40% de um ano escolar por aluno (ATKINSON et al, 2009). Outros autores são menos otimistas e enfatizam possí-veis efeitos negativos dos sistemas de incentivos, incluindo a erosão da motivação intrínseca inerente à docência pela motivação extrínseca mais instrumental. Springer (2009) menciona a perda do ambiente colaborativo e a instalação de interesses mais competitivos, ao mesmo tempo em que critica a incapacidade dos testes de retratar a complexidade multitarefa do trabalho do professor.…”
Section: Pesquisa Sobre Sistemas De Incentivo Monetáriounclassified
“…Given that good teachers are often attracted to schools with a high proportion of pupils from advantaged backgrounds, efforts to narrow the gaps between pupils from different backgrounds should consider ways to identify the best teachers (perhaps using CVA measures 20 ) and put in place systems and financial incentives to encourage them to move to, and remain at, the most disadvantaged schools (Nickell, 2004). One related avenue has been the introduction of merit pay for teachers, which has been found to have a positive impact on student achievement in some subjects in England (Atkinson et al, 2004). This avenue for encouraging higher teacher performance is promising, given the importance of teaching quality.…”
Section: Improve Incentives For Good Teachers To Go To Poor Schoolsmentioning
confidence: 99%